Clinicopathologic Features of CIC-NUTM1 Sarcomas, a New Molecular Variant of the Family of CIC-Fused Sarcomas. (February 2019) - Le Loarer, François; Pissaloux, Daniel; Watson, Sarah; Godfraind, Catherine; Galmiche-Rolland, Louise; Silva, Karen; Mayeur, Laetitia; Italiano, Antoine; Michot, Audrey; Pierron, Gaëlle; Vasiljevic, Alexandre; Ranchère-Vince, Dominique; et al.
Abstract : CIC -fused sarcomas represent an emerging family of tumors, for long connected to the Ewing family group of tumors, but underlined by distinct CIC fusions with different partners. 3′ Fusion partners include DUX4, FOXO4, and, as recently emphasized, NUTM1. In this study, we report the clinicopathologic and molecular features of a series of 6 CIC-NUTM1 sarcomas. Mean age at diagnosis was 6 years (2 to 27 y), and 4 patients were male individuals. Primary tumors were located in the central nervous system (n=3), paravertebral soft tissue and epidural spaces (n=1, each), and lung (n=1). Median overall survival was 17.5 months (7 to 37 mo), and all but one patient died of disease. All tumors displayed classic features of CIC-DUX4 sarcomas with round cell to epithelioid microscopic appearance. Most tumors expressed ETV4 and NUTM1 (n=5/6 and 6/6, respectively), whereas WT1cter was positive in only 2 cases. All tested tumors were positive for break-apart fluorescence in situ hybridization for CIC and NUTM1 . Apart from CIC or NUTM1 genomic breakpoints, no other recurrent copy number alteration was seen on genomic profiles. Fusion transcripts were identified by RNA-sequencing on either formalin-fixed paraffin-embedded or frozen material. CIC and NUTM1 breakpoints were located between exons 16 and 20 and exons 2 and 5, respectively. Altogether, CIC-NUTM1 sarcomas represent a new molecular variant of CIC -fused sarcomas with a predilection for the central nervous system and younger pediatric population. Its phenotype may be confused with NUT carcinomas. Abstract : Supplemental Digital Content is available in the text.